Growth and Pb Uptake of Brassica campestris Enhanced by Two Ecological Earthworm Species in Relation to Soil Physicochemical Properties - Tibihenda, Cevin; Zhang, Menghao; Zhong, Hesen; Xiao, Ling; Wu, Ling; Dai, Jun; Liu, Kexue; Zhang, Chi (Frontiers in Environmental Science, 2022)
This study evaluated the different influences of two ecological earthworm species on soil physicochemical properties, Pb bioavailability, and the growth and Pb accumulation of Brassica campestris in a Pb-contaminated soil. In a 30-day microcosm experiment, the anecic earthworm species Amynthas aspergillum and the epigeic species Eisenia fetida were inoculated in a soil artificially contaminated with Pb at different levels (i.e., 0, 100, 500, and 1000 mg·kg-1), and B. campestris was grown. Results showed A. aspergillum was more tolerant to Pb contamination than E. fetida. Earthworm inoculation significantly increased soil Eh, organic carbon, DOC, total nitrogen, and Pb bioavailability but decreased soil pH. Compared with the treatment with only B. campestris, the bioavailable Pb in the E. fetida+B. campestris treatment was significantly increased at the Pb contamination levels of 0 and 100 mg∙kg-1, respectively, and the bioavailable Pb in the A. aspergillum+B. campestris treatment was significantly increased at the 0 and 500 mg∙kg-1 Pb contamination levels, respectively. Compared with no earthworm inoculation, E. fetida inoculation significantly increased Pb content in the belowground parts of B. campestris and that in the aboveground parts at the 100 mg∙kg-1 Pb level. Principal component analysis (PCA) showed that earthworm inoculation exerted a stronger effect on soil properties than Pb contamination, but the latter had a stronger effect on plant growth and Pb accumulation. Compared with A. aspergillum, E. fetida had a greater effect on soil CEC, available Pb, and plant growth and Pb accumulation. In contrast, A. aspergillum had a greater effect on soil C and N contents than E. fetida. The co-inertia analysis revealed that plant Pb accumulation was positively correlated with soil available Pb and CEC, and that leaf chlorophyll concentration was closely related with soil Eh, pH, and DOC. The findings of this study showed that in Pb-contaminated soils, earthworm inoculation exerted a strong effect on soil physicochemical properties and the growth and Pb accumulation of the leafy vegetable B. campestris. Both the epigeic earthworm species E. fetida and the anecic species A. aspergillum were associated with higher bioavailable Pb accumulation or concentration, which may bring a possible risk on food security.